Theft of Cultural Property in the Context of the Polish Criminal Law - Katarzyna Banasik (Societas et Iurisprudentia, 2019)
The aim of this paper is to examine whether the Republic of Poland guarantees cultural property appropriate protection against theft under the criminal law. The author begins by analysing the 1972 Paris Convention Concerning the Protection of World Cultural and Natural Heritage and presenting the relevant regulations. In the next part of the paper, she analyses the legal grounds for classifying cultural property theft as a felony or a misdemeanour. Moreover, the author explains the term “cultural property” and its relationship with the term “cultural relic”. She also provides an exhaustive analysis of two particular elements of this category of theft: “property of considerable value” and “property of significant cultural value”. She concludes by assessing the current state of the Polish criminal law from the perspective of the protection of cultural property against theft.